Pengaruh Likuiditas dan Struktur Modal terhadap Kinerja Keuangan yang Dimediasi Green Accounting Disclosure pada Perusahaan Sub-Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Dela Wahyu Putri Awanda; Sunu Priyawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
As a key driver of national economic performance, the food and beverage sector continues to face various challenges in ensuring sustainability, particularly in relation to environmental and social responsibilities. This study seeks to examine the influence of liquidity and capital structure on financial performance, with green accounting disclosure serving as a mediating variable, among food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. The research employs a quantitative approach using structural equation modeling (SEM) based on partial least squares (PLS). The sample consists of 10 corporations selected through purposive sampling, utilizing secondary data obtained from sustainability reports and annual financial statements. Empirical evidence indicates that liquidity does not significantly affect financial performance, whereas capital structure and green accounting disclosure exert significant effects on financial performance. Additionally, liquidity significantly influences green accounting disclosure, while capital structure does not. The findings further reveal that green accounting disclosure effectively mediates the relationship between liquidity and financial performance but fails to mediate the relationship between capital structure and financial performance. Overall, this study underscores the importance of sound funding structure management and environmental transparency in enhancing financial performance and supporting sustainable business practices.